Representation of Kathoey in Thai Song Discourse: A Comparative Analysis of Self-Representation and External Perceptions - Sreejak, Thanawut (NIDA Journal of Language and Communication, 2025)
This study examines the representation of kathoey identity in Thai song discourse, comparing songs by kathoey and cisgender singers. Using a combination of corpus linguistics and queer linguistics, this study concentrates on linguistic patterns and thematic representations in two sub-corpora of Thai songs from 2004 to 2024. Key findings reveal that while cisgender singers’ songs frequently rely on stereotypes and external observations, kathoey-authored songs offer more nuanced portrayals of community dynamics, identity struggles, and lived experiences. This study uncovers novel themes such as intra-group discrimination, hierarchies within the kathoey community, and ageism. Additionally, this study critiques the perpetuation of cisgenderism in Thai song discourse, highlighting how language use can both challenge and reinforce existing power structures. Moreover, the increased use of the term kathoey in kathoey singers’ songs suggests an active linguistic reclamation process.